Respuestas
Respuesta dada por:
23
Hola.
![x^2+16x+64 x^2+16x+64](https://tex.z-dn.net/?f=x%5E2%2B16x%2B64)
![\left(x^2+8x\right)+\left(8x+64\right) \left(x^2+8x\right)+\left(8x+64\right)](https://tex.z-dn.net/?f=%5Cleft%28x%5E2%2B8x%5Cright%29%2B%5Cleft%288x%2B64%5Cright%29)
![x\left(x+8\right)+8\left(x+8\right) x\left(x+8\right)+8\left(x+8\right)](https://tex.z-dn.net/?f=x%5Cleft%28x%2B8%5Cright%29%2B8%5Cleft%28x%2B8%5Cright%29)
![\left(x+8\right)\left(x+8\right) \left(x+8\right)\left(x+8\right)](https://tex.z-dn.net/?f=%5Cleft%28x%2B8%5Cright%29%5Cleft%28x%2B8%5Cright%29)
---> Respuesta 1.
![2) x^2+8x+7 2) x^2+8x+7](https://tex.z-dn.net/?f=2%29+x%5E2%2B8x%2B7)
![\left(x^2+x\right)+\left(7x+7\right) \left(x^2+x\right)+\left(7x+7\right)](https://tex.z-dn.net/?f=%5Cleft%28x%5E2%2Bx%5Cright%29%2B%5Cleft%287x%2B7%5Cright%29)
![x\left(x+1\right)+7\left(x+1\right) x\left(x+1\right)+7\left(x+1\right)](https://tex.z-dn.net/?f=x%5Cleft%28x%2B1%5Cright%29%2B7%5Cleft%28x%2B1%5Cright%29)
---> Respuesta 2
¡Espero haberte ayudado, saludos...!
¡Espero haberte ayudado, saludos...!
Respuesta dada por:
6
X²+16x+64
x +8
x +8
8x+8x = 16x
(x+8)(x+8)
x²+8x+7
x +7
x +1
7x+ x = 8x
(x+7)(x+1)
x +8
x +8
8x+8x = 16x
(x+8)(x+8)
x²+8x+7
x +7
x +1
7x+ x = 8x
(x+7)(x+1)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años